The effect of audit opinions, implementation of audit recommendations, and findings of state losses on corruption levels in the ministries and institutions of the Republic of Indonesia - Budiman, Muhamad Agung; Amyar, Firdaus (Badan Pemeriksa Keuangan Republik Indonesia, 2021)
The prevalence of corruption in Indonesia is increasing every year. This fact has further undermined public confidence to strengthen governance and is a critical barrier to national development. This study aims to empirically examine the individual and combined impact of audit opinions, the implementation of audit recommendations, and findings of state losses by the Indonesian Supreme Audit Board (BPK) on the prevalence of corruption in ministries and institutions in the Republic of Indonesia. Using multiple linear regression analysis, this study used a purposive sampling method and investigated 72 ministries using secondary data from 2014 to 2017 obtained from BPK and the Corruption Eradication Commission of the Republic of Indonesia (KPK). This study indicates that audit opinions and the implementation of audit recommendations do not affect corruption in Indonesian ministries and institutions. In contrast, findings of state losses do have an influence. The combination of audit opinions, implementation of audit recommendations, and findings of simultaneous state losses do not affect corruption cases in Indonesian ministries and institutions. BPK can use the results of this study to formulate approaches and recommendations for auditing government financial reports that have a strong correlation with corruption eradication. Moreover, KPK needs to be more vigorous in its efforts to eradicate corruption, including establishing closer cooperation with BPK because the results of this research show that findings of state losses by BPK are closely related to corruption cases.